The phenomenon of creation of highly productive national science in a historically short period in Saudi Arabia and Qatar - F. A. Kurakov (Ekonomika Nauki)
The phenomenon of creation of highly productive national science during a historically short period (10 years) in Saudi Arabia and Qatar. The article presents the results of scientometric analysis of the publication flow in the Russian Federation, Qatar and Saudi Arabia, indexed in Scopus database for the period between 2011 to 2015 years. A comparison was completed of gross expenditure on research and development in these countries. It has shown that at lower national budgets on R & D Saudi Arabia and Qatar have achieved a much higher scientific productivity of domestic sciences in comparison with Russia. The article presents a review of action plan and directions of scientific-technological policy that allowed Saudi Arabia achieve a dynamic development of the national scientific and technological sector.